PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN NASABAH DALAM MEMILIH PRODUK TABUNGAN PADA PT. BANK BNI 46 TUPAREV CABANG CIREBON - Sumarsana, Asep; Supriyadi, Agung; Surono, Surono; Havidotinnisa, Siti; Atika, Atika (Fakultas Ekonomi dan Bisnis, 2023)
The purpose of this research is to analyze the effect of the marketing mix (Product, Price, Promotion, Location, People, Physical Facilities, and Process) on PT. Bank BNI Tuparev Cirebon Branch Office. This research was conducted at PT. Bank BNI Tuparev Cirebon Branch Office. Respondents of this study are savings customers of PT. Bank BNI Tuparev Cirebon Branch Office with a sample of 100 people. Research using multiple linear regression analysis with the help of SPSS. Conclusions from this study: 1. the marketing mix consisting of product, price/interest rate, promotion, location, people, physical evidence, and process together have a positive influence and significantly to customer decisions in choosing savings products at BNI Tuparev Bank Cirebon 2 Branch Office. Of the seven variables studied, only location and people have a positive and significant influence on customer decisions. 3. Other variables such as product, price/interest rate, promotion, physical evidence, and process do not show a significant effect on customer decisions. Therefore, companies need to focus on aspects of location and quality of employee service as an effort to increase the number of customers and improve customer decisions in choosing savings productsKey words: marketing mix, Saving Decision